Distribution and comparison of human papilloma virus genotype in cervical cancer in ecological region of Nepal. - Thapa,Sandeep
Background: Cervical cancer is the second leading cause of cancer related deaths, next only to breast cancer worldwide, but is easily preventable if detected early. It accounts for more than 270000 deaths annually and developing countries bear the burden of almost 85% of these cases. Campaign for cervical cancer screening has been carried out in Nepal since many years but it still stands in the world with respect to morbidity and mortality associated with cervical cancer. Method: After obtaining written informed consent, sociodemographic details including clinical history were obtained from the participants using a structured questionnaire. A speculum examination was carried out and cervical cells were collected and a conventional smear were prepared for cytological examination. Further, molecular examination was performed for the molecular characterization. Report: In this study, most of the patients belonged to the age group of 20-25 years and 30-35 years marking 19.67% which is trailed by 35-40 years (18.03%). Likewise, high prevalence of early marriage was reported with an average age of 17 years. Most of the patients experienced abdominal pain (28.6%) followed by chronic backpain (22.85%), and weakness (18.03%). In addition, only 15(12.29%) of women were screened positive on Pap smear. However, out of 107 Pap negative samples, 8 (7.47%) ware reported positive with molecular examination. Among them, five samples were stated with HPV 18 and three with HPV 16. Discussion: It has been well documented in recent years that providing quality assured and effective cervical cytology screening is a challenging task and cytology screening programs have been less successful in reducing cervical cancer. Moreover, this study will be useful for and guide eventual national scale up of HPV testing as a primary screening test in future. Keywords: Cervical cancer, molecular diagnosis, Pap smear, polymerase chain reaction, Nepal